Triglycerides and total cholesterol concentrations in association with IFG/IGT in Chinese adults in Qingdao, China - Cui, Jing (BMC Public Health, 2018)
BACKGROUND: To investigative the association of triglycerides (TG) and total cholesterol (TC) concentrations with impaired fasting glucose/ impaired glucose tolerance (IFG/IGT) in Chinese adults. METHODS: The population-based cross-sectional diabetes survey was conducted in 2006 and 2009 in Qingdao, separately. 4400 participants (1 793 men and 2607 women) were include in current analysis. IFG/IGT was defined according to fasting plasma glucose (FPG) and/or 2 h post-load plasma glucose (2 h PG). Logistic regression models and areas under receiver operating characteristic curves (AUROC) were performed to estimate the associations between TG, TC levels and IFG/IGT. RESULTS: Spearman analysis showed that serum TG and TC was independently and positively associated with FPG and 2 h PG. As compared with normoglycaemia, the odds ratio[(95% confidence intervals), OR(95%CI)] for IFG/IGT corresponding to hypertriglyceridemia (HTG) were 1.61 (1. 17, 2. 22) in men and 1.57(1.15, 2.14) in women for TG and accompany with Hypercholesterolemia (HTC) 1.56 (1.15, 2.13) and 1. 20 (0.93, 1.54) for TC, when adjusting for confounding factor. The AUROCs of TG, TC for IFG/IGT were relatively smaller (0.50 < AUROC< 0. 7) in both gender. The optimal cut-offs for TG and TC was 1.61, 4.91 in men and 1. 24, 5. 32 in women, respectively. CONCLUSIONS: Evaluated TG in both gender and TC in men were independently associated with the present of the IFG/IGT, yet, could not be an authentic predictors of IFG/IGT in both men and women in current Chinese population.